(untitled) (World Economics and Finance Bulletin, 2025)
This investigation intended to investigate the way that financial culture affects the participants’ financial situation through behavior. Staff and faculty from the Faculty of Administration and Economics, the Imam Kazim College (peace be upon him), the Najaf Ashraf College, and the University of Kufa participated in the investigation. These participants, the subject of the research, were interested in how they manage their daily finances and expenditures. The importance of financial literacy and its significance in financial management should be paramount. As a result, the participants in research must recognize and take full advantage of the value of increasing their financial knowledge in order to more effectively manage their resources and have a more secure future. The difference between people’s financial knowledge and their capacity to take advantage of opportunities and make informed decisions in financial matters is increasing. As a result, in today’s financial climate, financial literacy continues to be a significant obstacle to individuals’ financial behavior and the efficiency of investment. As a result, the researchers attempted to determine if participants’ financial literacy, via their actions, affects their own financial stability. The investigation’s subjects were employees of TBI Rafidain Bank, a specialized bank that specializes in Iraq’s financial sector. Each employee associated with the bank was considered to be an independent entity. A total of 160 questionnaires were sent to the population, of which 156 were returned. The methodology of research was based on SPSS 23.0. As a result, financial culture has a significant role in the financial management of the sample and promotes the personal financial situation of individuals through their actions.